PARTISIPASI ANGGOTA KELOMPOK TANI CITRA DALAM MENINGKATKAN PRODUKSI KANGKUNG DARAT DI DESA AIMOLI KECAMATAN ALOR BARAT LAUT (ABAL) - Emi Rensiana Latuan; Ferdinan Demang (Politeknik Pertanian Negeri Kupang, 2022)
Determination of Example Villages is done intentionally (Purposive Sampling), with the consideration that the Citra Group is a long-established farmer group and is now still active in carrying out activities of groundwater spinach farming. Determination of respondents is done by using saturated samples, a total sample of 25 people. The analysis showed that: (1) The participation of Citra farmer group members in increasing the production of groundwater spinach was classified as high with an average score of 83% in achieving the maximum score. This means that farmer group members have good participation (2) The average productivity of ground kale from Citra farmer group members from September to October 2021 is 787 bunches/are. Keywords: Participation, Spinach, Kale Kale Production.